The impact of Independent Power Producers on electricity generation capacity, tariff and access in Sub-Saharan Africa - Mhlanga,Mduduzi (Graduate School of Business (GSB), 2021)
Sub-Saharan Africa is the most electricity-poor region in the world with an estimated 62.5 percent or just above 600 million people without access to electricity and those who have access, are connected to an unreliable system that does not meet their energy needs. The introduction of Independent Power Producers (IPPs) is perceived to be the panacea to all the sector's problems in that it will attract much-needed private investment, increase generation capacity, reduce electricity tariffs due to efficiency and competition and ultimately increase the rate of access to electricity by the general population for the region. This study examined the impact of IPPs on electricity generation growth, tariffs and access in 48 countries in Sub- Saharan Africa using panel data from 1990 to 2013. The findings suggest that over the 23-year period, only 40 percent of the sampled countries had used IPPs for power generation. In addition, results from the panel regression estimations confirmed that the use of IPPs has increased regarding electricity generation growth and electricity access in Sub-Saharan Africa and also led to a reduction in electricity tariff. The policy implication of this study is that Sub- Saharan African countries should allow for the participation of IPPs to achieve increased generation capacity, reduction of tariffs and increased access to electricity by the general population.